bis-Silyl-triazenide ligands in alkaline-earth metal chemistry - Knüpfer, Christian; Langer, Jens; Harder, Sjoerd (Zeitschrift für Anorganische und Allgemeine Chemie, 2023)
Monoanionic N,N-chelating triazenide ligands, [R-NNN-R]−, are compared to formamidinate or β-diketiminate ligands considerably less electron-donating and therefore potentially suitable for stabilizing electron rich metals in low oxidations states. A feature reported for silyl-substituted triazenide ligands, is their ability to eliminate N2 resulting in (R3Si)2N− anions. Here we describe a series of group 1 and 2 metal complexes with the very bulky bis-silyl-triazenide ligand [tBu3Si-NNN-SitBu3]−. Heteroleptic complexes could be isolated for Mg: [(tBu3Si)2N3]MgnBu2 or [(tBu3Si)2N3]MgI2, including its ether adducts. Despite bulky silyl substituents, the ligand did not stabilize heteroleptic [(tBu3Si)2N3]AeN(SiMe3)2 complexes for Ca, Sr and Ba and only homoleptic Ae[(tBu3Si)2N3]2 complexes were isolated. Thermal decomposition of these complexes did result in N2 elimination and formation of the expected amide complexes. Reduction of [(tBu3Si)2N3]MgI ⋅ (Et2O) with KC8 in Et2O led to the formation of a MgI complex with a Mg−Mg bond length of 2.902(1) Å. As only one of the Mg centres shows coordination with a Et2O ligand, this is a rare example of an asymmetric Mg−Mg bond. This MgI complex is rather unstable in benzene solution, likely due to reduction of the ligand system. Triazenide ligands are therefore not suitable for stabilization of group 2 metals in low oxidation states.
CRIS-Team Scopus Importer:2023-12-29
Keywords: Alkaline-earth; Low-valent; Reduction; Silyl; Triazene

Carbon-Halogen Bond Activation with Powerful Heavy Alkaline Earth Metal Hydrides - Wiesinger, Michael; Rösch, Bastian; Knüpfer, Christian; Mai, Jonathan; Langer, Jens; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2021)
Reaction of [(DIPePBDI)SrH]2 with C6H5X (X=Cl, Br, I) led to hydride-halogenide exchange (DIPePBDI=HC[(Me)CN-2,6-(3-pentyl)phenyl]2). Conversion rates increase with increasing halogen size (F<Cl<Br<I). Reaction of [(DIPePBDI)SrH]2 with C6H5F was slow and ill-defined but addition of C6H4F2 gave smooth hydride-fluoride exchange. After addition of THF the full range of Sr halogenides was structurally characterized: [(DIPePBDI)SrX ⋅ THF]2 (X=F, Cl, Br, I). Mixtures of AeN“2 and PhSiH3 in situ formed less defined but more robust Ae metal hydride clusters (AexN”yHz, Ae=Ca, Sr, Ba and N“=N(SiMe3)2) which are able to hydrodefluorinate C6H5F. Conversion rates increase with increasing metal size (Ca<Sr<Ba). Also alkylfluorides (1-F-hexane, F-cyclohexane, 1-F-adamantane) could be converted but, due to solubility problems of the Ba species, the fastest conversion was found for Sr. These AeN”2/PhSiH3 mixtures also converted SF6 at room temperature to give undefined decomposition products. Addition of Me6Tren to a SrN“2/PhSiH3 led to crystallization of [Sr6N”2H9 ⋅ (Me6Tren)3+][SrN“3−]; Me6Tren=tris[2-(dimethylamino)ethyl]amine). After hydrodefluorination, Sr6N”4F8 ⋅ (Me6Tren)2 was formed and structurally characterized. Dissolution in THF led to cluster growth and the larger cluster Sr16N“8F24 ⋅ (THF)12 is structurally characterized. DFT calculations support that hydrodehalogenation of halobenzenes follows a concerted nucleophilic aromatic substitution mechanism (cSNAr).
CRIS-Team Scopus Importer:2021-08-27
Keywords: Alkaline-earth metal; DFT calculation; Hydride; Hydrodehalogenation

Early Main Group Metal Catalysts for Imine Hydrosilylation - Elsen, Holger; Fischer, Christian; Knüpfer, Christian; Escalona, Ana; Harder, Sjoerd (Chemistry - A European Journal, 2019)
The efficient catalytic reduction of imines with phenylsilane is achieved by using the potassium, calcium and strontium based catalysts [(DMAT)K (THF)]∞, (DMAT)2Ca⋅(THF)2 and (DMAT)2Sr⋅(THF)2 (DMAT=2-dimethylamino-α-trimethylsilylbenzyl). Eight different aldimines and the ketimine Ph2C=NPh could be successfully reduced by PhSiH3 at temperatures between 25–60 °C with catalyst loadings down to 2.5 mol %. Also, simple amides like KN(SiMe3)2 or Ae[N(SiMe3)2]2 (Ae=Ca, Sr, Ba) catalyze this reaction. Activities increase with metal size. For most substrates the activity increases along the row K
CRIS-Team Scopus Importer:2019-11-29
Keywords: alkaline earth metals; density functional calculations; hydrosilylation; imines; potassium

Heterometallic Mg−Ba Hydride Clusters in Hydrogenation Catalysis - Wiesinger, Michael; Knüpfer, Christian; Elsen, Holger; Mai, Jonathan; Langer, Jens; Harder, Sjoerd (ChemCatChem, 2021)
Reaction of a MgN“2/BaN”2 mixture (N“=N(SiMe3)2) with PhSiH3 gave three unique heterometallic Mg/Ba hydride clusters: Mg5Ba4H11N”7 ⋅ (benzene)2 (1), Mg4Ba7H13N“9 ⋅ (toluene)2 (2) and Mg7Ba12H26N”12 (3). Product formation is controlled by the Mg/Ba ratio and temperature. Crystal structures are described. While 3 is fully insoluble, clusters 1 and 2 retain their structures in aromatic solvents. DFT calculations and AIM analyses indicate highly ionic bonding with Mg−H and Ba−H bond paths. Also unusual H−⋅⋅⋅H− bond paths are observed. Catalytic hydrogenation with MgN“2, BaN”2 and the mixture MgN“2/BaN”2 has been studied. Whereas MgN“2 is only active in imine hydrogenation, alkene and alkyne hydrogenation needs the presence of Ba. The catalytic activity of the MgN”2/BaN“2 mixture lies in general between that of its individual components and strong cooperative effects are not evident.
CRIS-Team Scopus Importer:2021-09-17
Keywords: alkaline earth metal; catalysis; DFT calculations; heterometallic; hydride

Highly Active Superbulky Alkaline Earth Metal Amide Catalysts for Hydrogenation of Challenging Alkenes and Aromatic Rings - Martin, Johannes; Knüpfer, Christian; Eyselein, Jonathan; Färber, Christian; Grams, Samuel; Langer, Jens; Thum, Katharina; Wiesinger, Michael; Harder, Sjoerd (Angewandte Chemie International Edition, 2020)
Two series of bulky alkaline earth (Ae) metal amide complexes have been prepared: Ae[N(TRIP)2]2 (1-Ae) and Ae[N(TRIP)(DIPP)]2 (2-Ae) (Ae=Mg, Ca, Sr, Ba; TRIP=SiiPr3, DIPP=2,6-diisopropylphenyl). While monomeric 1-Ca was already known, the new complexes have been structurally characterized. Monomers 1-Ae are highly linear while the monomers 2-Ae are slightly bent. The bulkier amide complexes 1-Ae are by far the most active catalysts in alkene hydrogenation with activities increasing from Mg to Ba. Catalyst 1-Ba can reduce internal alkenes like cyclohexene or 3-hexene and highly challenging substrates like 1-Me-cyclohexene or tetraphenylethylene. It is also active in arene hydrogenation reducing anthracene and naphthalene (even when substituted with an alkyl) as well as biphenyl. Benzene could be reduced to cyclohexane but full conversion was not reached. The first step in catalytic hydrogenation is formation of an (amide)AeH species, which can form larger aggregates. Increasing the bulk of the amide ligand decreases aggregate size but it is unclear what the true catalyst(s) is (are). DFT calculations suggest that amide bulk also has a noticeable influence on the thermodynamics for formation of the (amide)AeH species. Complex 1-Ba is currently the most powerful Ae metal hydrogenation catalyst. Due to tremendously increased activities in comparison to those of previously reported catalysts, the substrate scope in hydrogenation catalysis could be extended to challenging multi-substituted unactivated alkenes and even to arenes among which benzene.
CRIS-Team Scopus Importer:2020-04-03
Keywords: Alkaline Earth Metals; Alkenes; Aromatic rings; DFT calculations; Hydrogenation

Lithium Aluminium Hydride and Metallic Iron: A Powerful Team in Alkene and Arene Hydrogenation Catalysis - Knüpfer, Christian; Färber, Christian; Langer, Jens; Harder, Sjoerd (Angewandte Chemie International Edition, 2023)
Alkenes that normally do not react with LiAlH4 (3-hexene, cyclohexene, 1-Me-cyclohexene), can be reduced to the corresponding alkanes by a mixture of LiAlH4 and Fe0 (the iron was activated by Metal-Vapour-Synthesis). This alkene-to-alkane conversion with a stoichiometric quantity of LiAlH4/Fe0 does not need quenching with water or acids, implying that both H's originate from LiAlH4. The LiAlH4/Fe0 combination is also a remarkably potent cooperative catalyst for hydrogenation of multi-substituted alkenes and benzene or toluene. An induction period of circa two hours and the minimally required temperature of 120 °C, suggests that the actual catalyst is a combination of Fe0 and the decomposition product of LiAlH4 (LiH and Al0). A thermally pre-activated LiAlH4/Fe0 catalyst did not need an induction time and is also active at room temperature and 1 bar H2. A combination of AliBu3 and Fe0 is an even more active hydrogenation catalyst. Without pre-activation, tetra-substituted alkenes like Me2C=CMe2 and toluene could be fully hydrogenated.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Aluminium; Hydrides; Hydrogenation; Iron; Sustainability

Metallic Barium: A Versatile and Efficient Hydrogenation Catalyst - Stegner, Philipp; Färber, Christian; Zenneck, Ulrich; Knüpfer, Christian; Eyselein, Jonathan; Wiesinger, Michael; Harder, Sjoerd (Angewandte Chemie International Edition, 2020)
Ba metal was activated by evaporation and cocondensation with heptane. This black powder is a highly active hydrogenation catalyst for the reduction of a variety of unactivated (non-conjugated) mono-, di- and tri-substituted alkenes, tetraphenylethylene, benzene, a number of polycyclic aromatic hydrocarbons, aldimines, ketimines and various pyridines. The performance of metallic Ba in hydrogenation catalysis tops that of the hitherto most active molecular group 2 metal catalysts. Depending on the substrate, two different catalytic cycles are proposed. A: a classical metal hydride cycle and B: the Ba metal cycle. The latter is proposed for substrates that are easily reduced by Ba0, that is, conjugated alkenes, alkynes, annulated rings, imines and pyridines. In addition, a mechanism in which Ba0 and BaH2 are both essential is discussed. DFT calculations on benzene hydrogenation with a simple model system (Ba/BaH2) confirm that the presence of metallic Ba has an accelerating effect.
CRIS-Team Scopus Importer:2020-12-25
Keywords: alkaline earth metals; barium; hydride; hydrogenation catalysis; metal activation

s-Block metal complexes of superbulky (tBu3Si)2N-: a new weakly coordinating anion? - Knüpfer, Christian; Klerner, Lukas; Mai, Jonathan; Langer, Jens; Harder, Sjoerd (Chemical Science, 2024)
Sterically hindered amide anions have found widespread application as deprotonation agents or as ligands to stabilize metals in unusual coordination geometries or oxidation states. The use of bulky amides has also been advantageous in catalyst design. Herein we present s-block metal chemistry with one of the bulkiest known amide ligands: (tBu3Si)2N- (abbreviated: tBuN-). The parent amine (tBuNH), introduced earlier by Wiberg, is extremely resistant to deprotonation (even with nBuLi/KOtBu superbases) but can be deprotonated slowly with a blue Cs+/e- electride formed by addition of Cs0 to THF. (tBuN)Cs crystallized as a separated ion-pair, even without cocrystallized solvent. As salt-metathesis reactions with (tBuN)Cs are sluggish and incomplete, it has only limited use as an amide transfer reagent. However, ball-milling with LiI led to quantitative formation of (tBuN)Li and CsI. Structural characterization shows that (tBuN)Li is a monomeric contact ion-pair with a relatively short N-Li bond, an unusual T-shaped coordination geometry around N and extremely short Li?Me anagostic interactions. Crystal structures are compared with Li and Cs complexes of less bulky amide ligands (iPr3Si)2N- (iPrN-) and (Me3Si)2N- (MeN-). DFT calculations show trends in the geometries and electron distributions of amide ligands of increasing steric bulk (MeN- < iPrN- < tBuN-) and confirm that tBuN- is a rare example of a halogen-free weakly coordinating anion.
CRIS-Team Scopus Importer:2024-03-15

Synthesis of Superbulky Amide Ligands by Addition of Polar Reagents to Sila–Imine - Knüpfer, Christian; Klerner, Lukas; Raucheisen, Michael; Langer, Jens; Harder, Sjoerd (Chemistry - A European Journal, 2024)
The chemistry of extremely bulky amide ligands is troubled by difficulties in deprotonation of the parent amine. As an alternative route to superbulky amide reagents, the addition of polar reagents to a sila–imine has been investigated. Attempts to synthesize the superbulky amide anion (tBu3Si)2N− by addition of tBuLi to tBu2Si=N(SitBu3) failed and gave tBu3Si(tBu2HSi)NLi and isobutene. Reaction of the sila–imine with KOtBu successfully led to tBu3Si[tBu2(tBuO)Si]NK which crystallized as a separated ion–pair. Reaction with the slightly bulkier KOAd (Ad=1-adamantyl) led in presence of THF to ether ring–opening. Reaction with tBuOH gave tBu3Si[tBu2(tBuO)Si]NH but this amine cannot be easily deprotonated. Reaction with (BDI*)MgnBu in presence of THF gave (BDI*)Mg+ ⋅ (THF)2 and the non–coordinating anion tBu3Si[tBu2(nBu)Si]N−; BDI*=ß-diketiminate ligand HC[C(tBu)N−DIPP]2, DIPP=2,6-diisopropylphenyl. Reaction of Mg(nBu)2 with tBu2Si=N(SitBu3) led to a Mg complex with one amide ligand: tBu3Si[tBu2(nBu)Si]N−. The other superbulky amide anion isomerized by internal deprotonation of a tBu-substituent to give a primary carbanion that is also coordinated to Mg. Although the amide–to–carbanion isomerization is highly contrathermodynamic, it allows for coordination of both anions to a single Mg center. The new bulky amides are rare cases of halogen–free weakly coordinating anions.
CRIS-Team Scopus Importer:2024-04-19
Keywords: Amide ligands; bulky ligands; s-block metals; weakly coordinating anion

Teaming up main group metals with metallic iron to boost hydrogenation catalysis - Färber, Christian; Stegner, Philipp; Zenneck, Ulrich; Knüpfer, Christian; Bendt, Georg; Schulz, Stephan; Harder, Sjoerd (Nature Communications, 2022)
Hydrogenation of unsaturated bonds is a key step in both the fine and petrochemical industries. Homogeneous and heterogeneous catalysts are historically based on noble group 9 and 10 metals. Increasing awareness of sustainability drives the replacement of costly, and often harmful, precious metals by abundant 3d-metals or even main group metals. Although not as efficient as noble transition metals, metallic barium was recently found to be a versatile hydrogenation catalyst. Here we show that addition of finely divided Fe-0, which itself is a poor hydrogenation catalyst, boosts activities of Ba-0 by several orders of magnitude, enabling rapid hydrogenation of alkynes, imines, challenging multi-substituted alkenes and non-activated arenes. Metallic Fe-0 also boosts the activity of soluble early main group metal hydride catalysts, or precursors thereto. This synergy originates from cooperativity between a homogeneous, highly reactive, polar main group metal hydride complex and a heterogeneous Fe-0 surface that is responsible for substrate activation.
CRIS-Team WoS Importer:2022-07-01